TRADITIONAL LEAFY VEGETABLES IN SENEGAL: DIVERSITY AND MEDICINAL USES - Mathieu, Gueye; Meissa, Diouf (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Six administrative regions of Senegal were investigated. Forty species of vegetable leaves which are traditionally consumed in Senegal have been inventoried. All species are members of twenty-one families the most numerous of which are Amaranthaceae Juss., Malvaceae Juss., Moraceae Link., the Papilionaceae Giseke and Tiliaceae Juss. The species are subdivided into three groups: cultivated leafy vegetables, plants gathered annually, perennial sub-ligneous and ligneous species. The gathered species represent 67.5% of the inventory, 40.7% of which is ligneous. Cultivated species account for 32.5% of the inventory. The species are consumed for their medicinal properties, nutritive value and eating habits linked to specific ethnic traditions. During the drought years, with the scarcity of main food (millet, mays) consumption of leafy vegetables is high. All species reported except Sesuvium portulacastrum L. are consumed like vegetable herbs. The species of Hibiscus are eaten in spinach and condiment form while Sesuvium portulacastrum L is cooked in salad. Of the forty species examined, eleven are widely consumed. Within the entire study area, Hibiscus sabdariffa predominates among species consumed, followed by Moringa oleifera Lam. and Senna obtusifolia Link. A high consumption level of some species like amarante, Corchorus tridens L., Corchorus aestuans L., Leptadenia hastata Decne. and Vigna unguiculata (L.) Walp is confined to certain areas. In addition to their consumption as vegetables, the medicinal uses of 57.5% of these is of primary importance. The most commonly exploited parts are, respectively, leaf (40%), roots (20%), and bark (13.3%). Among the numerous pathologies treated, abscess, constipation, and rheumatism are predominant followed by aphrodisiac uses. The Amaranthus spp. L., Leptadenia hastata Decne., Senna obtusifolia Link., Adansonia digitata L. and Tamarindus indica L. are species with multiple medicinal uses.